Beberapa Isu Teologi dan Syari’ah dalam Perspektif Islam dan Agama Samawi Lainnya: Studi Kasus Pemikiran M. Quraish Shihab - Ahmad Zainal Abidin; Thoriqul Aziz; Dewi Charisun Chayati (JOURNAL OF QUR'AN AND HADITH STUDIES, 2020)
This article discusses the comparison of  Islamic perspective and other religious perspectives regarding  some theological and sharia issues, taking Quraish Shihab’s thought as a case in point. Using a descriptive-analytic method, this study answers how his thoughts about some issues of theology and shari’a are similar with or different from other religious perspectives. This article finds that the theological and sharia themes that are carried by M. Quraish Shihab are related to texts such as in other religions, especially through the theme of unifying God, respecting for others, establishing prayer, prohibition of killing and doing heinous, qishāsh law, fasting, spirituality, and alms. Intertextual thinking is useful for bringing together interfaith themes that emphasize the unity of sources and the close relation of religions to one another.